Isotretinoin exposure in pregnant women in Korea - Nae Ry Kim; So Ra Yoon; June Seek Choi; Hyun Kyong Ahn; So-Young Lee; Dal Soo Hong; Jeong Sup Yun; Seong Yeon Hong; Yoon Ha Kim; Jung Yeol Han (Obstetrics & Gynecology Science, 2018)
ObjectiveIsotretinoin is a notorious teratogen otherwise used for the treatment of acne vulgaris. Some countries, including those in North America and the European Union, implemented the pregnancy prevention program (PPP); however, no PPP has yet been established in South Korea. So the aim of this study was to evaluate the rate of pregnant women exposed to isotretinoin among the callers of the Korean Mother Safe Counseling Center.MethodsThis is a prospective cohort study. We evaluated the demographic characteristics, obstetric history, and isotretinoin exposure of pregnant women based on the mother safe registry from April 2010 to July 2016.ResultsAmong 22,374 callers, 650 (2.9%) pregnant women were exposed to isotretinoin. The mean age was 29.0±4.4 years in the isotretinoin-exposed group and 32.0±4.2 years in the unexposed group (P<0.001). Moreover, the incidence of pregnancies within 30 days after isotretinoin discontinuation or during isotretinoin intake was 78.9% (513/650). The median duration of isotretinoin exposure was 18 (1–4,231) days. Furthermore, from 2011 to 2015, the incidence of isotretinoin exposure was 2.9±1.2 pregnancies per 10,000 births in South Korea.ConclusionApproximately 80% of pregnant women are exposed to isotretinoin within the recommended 30 days of contraception or during pregnancy. Therefore, the PPP has to be established in South Korea.